Consumer and clinician perspectives on personalising breast cancer prevention information. (February 2019) - Keogh, L.A.; Steel, E.; Weideman, P.; Butow, P.; Collins, I.M.; Emery, J.D.; Mann, G.B.; Bickerstaffe, A.; Trainer, A.H.; Hopper, L.J.; Phillips, K.A.
Abstract: Background: Personalised prevention of breast cancer has focused on women at very high risk, yet most breast cancers occur in women at average, or moderately increased risk (≤moderate risk). Objectives: To determine; 1) interest of women at ≤ moderate risk (consumers) in personalised information about breast cancer risk; 2) familial cancer clinicians' (FCCs) perspective on managing women at ≤ moderate risk, and; 3) both consumers' and FCCs reactions to iPrevent, a personalised breast cancer risk assessment and risk management decision support tool. Methods: Seven focus groups on breast cancer risk were conducted with 49 participants; 27 consumers and 22 FCCs. Data were analysed thematically. Results: Consumers reported some misconceptions, low trust in primary care practitioners for breast cancer prevention advice and frustration that they often lacked tailored advice about breast cancer risk. They expressed interest in receiving personalised risk information using iPrevent. FCCs reported an inadequate workforce to advise women at ≤ moderate risk and reacted positively to the potential of iPrevent to assist. Conclusions: While highlighting a potential role for iPrevent, several outstanding issues remain. For personalised prevention of breast cancer to extend beyond women at high risk, we must harness women's interest in receiving tailored information about breast cancer prevention and identify a workforce willing to advise women. Highlights: Increased demand from women at ≤ moderate risk for breast cancer risk advice. Demand not matched by a clinician group willing and able to provide advice. Despite 'hype' about breast cancer, women displayed misunderstandings about risk. Consumers felt the need to attend a PCP to access risk advice would limit usefulness. Consumers and clinicians thought iPrevent could play a beneficial role in prevention.